PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS OF TIME MANAGEMENT TECHNOLOGY IN DEVELOPING STUDENTS’ INDEPENDENT LEARNING COMPETENCE (International Conference on Education, Psychology and Humanities, 2026)
In this study, the role of time management technology in developing students’ independent learning competence was analyzed based on the integration of pedagogical and psychological approaches. During the research process, methods such as system analysis, comparative analysis, modeling, and pedagogical observation were employed. Within the pedagogical approach, the role of didactic tools in enhancing student engagement was examined, while the psychological approach was analyzed based on the self-regulated learning model. The results demonstrated that components such as planning, time allocation, monitoring, and reflection are key factors in the formation of students’ independent learning competence. At the conclusion of the study, it was substantiated that time management technology serves as a mechanism integrating pedagogical and psychological approaches. The systematic implementation of this technology in the educational process contributes to improving students’ self-regulation, independent learning, and professional development.
Keywords: time management, independent learning, self-directed learning, competence, pedagogical approach, psychological approach, self-regulated learning, planning, time allocation, reflection, instructional tools.